ANALISIS PENGELOLAAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PINRANG - Rustan Rustan; Muttiarni Muttiarni (Jurnal Riset Perpajakan: Amnesty, 2018)
This research aims to know the financial management of the public sector can support the financial performance of the Government of district Pinrang, the method of data analysis used in this research is a qualitative method. Financial management is calculated based on 5 ratios i.e. regional financial self-reliance ratio, PAD capability, compatibility ratio, and growth ratio. The results showed that the regional financial independence ratio over the past five years resulted in an average number of 3.97% with an instructive pattern of relationships. Meanwhile, the average PAD capability is only 5.047% with a pattern of financial capability that is still in intervals of 00.01%-the ability PAD to finance the area's regular expenditure, often referred to by the average IKR (routine capability index) ratio Only 5.047% with a pattern of financial capability that is still in intervals of 00.01%-the average result of the development ratio of 19.50% and the routine spending ratio of 8.05%